Pharmacological management of abnormal tone and movement in cerebral palsy. Issue 8 (4th August 2019) - Lumsden, Daniel E; Crowe, Belinda; Basu, Anna; Amin, Sam; Devlin, Anita; DeAlwis, Yasmin; Kumar, Ram; Lodh, Rajib; Lundy, Claire T; Mordekar, Santosh R; Smith, Martin; Cadwgan, Jill
Abstract : Background: The evidence base to guide the pharmacological management of tone and abnormal movements in cerebral palsy (CP) is limited, as is an understanding of routine clinical practice in the UK. We aimed to establish details of motor phenotype and current pharmacological management of a representative cohort across a network of UK tertiary centres. Methods: Prospective multicentre review of specialist motor disorder clinics at nine UK centres, collecting data on clinical features and pharmacological management of children and young people (CYP) with CP over a single calendar month. Results: Data were collected from 275 CYP with CP reviewed over the calendar month of October 2017. Isolated dystonia or spasticity was infrequently seen, with a mixed picture of dystonia and spasticity ± choreoathetosis identified in 194/275 (70.5%) of CYP. A comorbid diagnosis of epilepsy was present in 103/275 (37.4%). The most commonly used medications for abnormal tone/movement were baclofen, trihexyphenidyl, gabapentin, diazepam and clonidine. Medication use appeared to be influenced separately by the presence of dystonia or spasticity. Botulinum toxin use was common (62.2%). A smaller proportion of children (12.4%) had undergone a previous neurosurgical procedure for tone/movement management. Conclusions: CYP with CP frequently present with a complex movement phenotype and comorbid epilepsy. They have multiple therapy, medical and surgical management regimens. Future trials of therapeutic, pharmacological or surgical interventions in this population must adequately encompass this complexity in order to be translatable to clinical practice.